Comparison of prognostic models for burn patients: A retrospective nationwide registry study. Issue 8 (December 2020) - Yoshimura, Yuya; Saitoh, Daizoh; Yamada, Kohei; Nakamura, Takahiro; Terayama, Takero; Ikeuchi, Hisashi; Sasaki, Junichi; Nemoto, Manabu
Highlights: Prognostic burn score (PBI) is a unique prediction model in Japan where other prognosis scores are rarely used. This nationwide retrospective study compared the accuracy of burn prognosis models in Japanese burn patients. Although PBI was an excellent prognostic score, it was not superior to Baux score, revised Baux score, and ABSI. The Baux score, which is simple and accurate, is a clinically valuable prognosis prediction model in Japan. Abstract: Background: Prognostic burn index (PBI) is a unique model utilized to predict mortality of burn patients in Japan. In contrast, other prediction models are rarely used in Japan, and their accuracy and predictive value are unknown. The present study aimed to compare commonly used burn prediction models and determine the appropriate model for mortality prediction in Japanese burn patients. Methods: Japanese burn patients registered in the nationwide burn registry of Japanese Society for Burn Injury between April 1, 2011 and March 31, 2019 were reviewed retrospectively. The prognostic performance of PBI was compared with Baux score, revised Baux score, abbreviated burn severity index (ABSI), Ryan score and Belgian outcome in burn injury score (BOBI). The primary outcome was in-hospital mortality. Results: The study included 7911 acute burn patients. The overall mortality rate was 10.7%, the median age was 52 (interquartile range, 26–72) years, and the median % total body surface area was 7% (interquartile range, 3%–17%). The areas under the receiver operating characteristic curve for PBI, Baux score, ABSI, revised Baux score, Ryan score, and BOBI were 0.940 (95% confidence interval [CI]: 0.931–0.948), 0.943 (95% CI: 0.934–0.951; p  = 0.002), 0.945 (95% CI: 0.937–0.953; p  = 0.058), 0.946 (95% CI: 0.937–0.953; p  = 0.002), 0.859 (95% CI: 0.846–0.870; p  < 0.001), and 0.896 (95% CI: 0.885–0.905; p  < 0.001), respectively. Conclusion: Although the performance of PBI was good, it was not superior to the Baux score, revised Baux score, and ABSI. These three scores have a high prognostic accuracy. Hence, they are considered as alternative burn prognostic scores in Japan. The Baux score was an optimal prognostic model for patients with burns in Japan.